Self-esteem, coping strategies and views on masculinity among selected househusbands in Jaro, Iloilo City - Asperga, Altheamae V.; Escoto, Mia Frances
This descriptive study which sought to determine the following: (1) the levels of self-esteem among househusbands, (2)their coping strategies towards problems and stress, (3) and their views on the concept of masculinity., Twenty-eight househusbands with wives working abroad participated in the study. The research utilized the Rosenberg Self-esteem Scale, the COPE Inventory, and a masculinity scale to measure the three variables respectively. The results yielded a high level of self-esteem for these househusbands. For the coping strategies, it was found out that the three most often used coping styles were that of religious, followed by planning, and active coping. The least employed was the substance use coping probably because it is highly associated with being an irresponsible father and husbands. On the other hand, there was no significant difference found between the househusbands' who had traditional and progressive views on masculinity.
Thesis (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Husbands -- Jaro, Iloilo City, Philippines